Gry Joanny Chmielewskiej = Games o Joanna Chmielewska - Gazdecka, Elżbieta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper discusses various types of games used in the works of Joanna Chmielewska. The author focuses on discussing three out of four game and microgame categories discerned by R. Caillois that appear in literary output of Chmielewska. The paper fits into the current discussion on the meaning of term "game" in literary studies.
Keywords: Chmielewska, Joanna (1932-2013); gra; play; games